2014
DOI: 10.1002/ijc.29140
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin‐1 and polycystin‐2 are involved in the acquisition of aggressive phenotypes in colorectal cancer

Abstract: The polycystins PC1 and PC2 are emerging as major players in mechanotransduction, a process that influences all steps of the invasion/metastasis cascade. We hypothesized that PC1 and PC2 facilitate cancer aggressiveness. Immunoblotting, RT-PCR, semi-quantitative and quantitative real-time PCR and FACS analyses were employed to investigate the effect of polycystin overexpression in colorectal cancer (CRC) cells. The impact of PC1 inhibition on cancer-cell proliferation was evaluated through an MTT assay. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 43 publications
9
75
0
Order By: Relevance
“…81 Polycystins have been also associated with cancer and have recently emerged as novel prognostic tools in colorectal tumors. 82,83 Unpublished data from our laboratory indicate that modulation of PC1 activity affects cell migration and proliferation in MG-63 cells. In addition, Adamopoulos et al Signal transduction in osteosarcoma 1301 stable downregulation of Polycystic Kidney Disease 1 gene in MG-63 cells enhances cell proliferation and affects proper cell differentiation, alterations mediated through impaired intracellular calcium-cAMP regulation, and activation of PKA.…”
Section: Mechanotransduction and Os Developmentmentioning
confidence: 99%
“…81 Polycystins have been also associated with cancer and have recently emerged as novel prognostic tools in colorectal tumors. 82,83 Unpublished data from our laboratory indicate that modulation of PC1 activity affects cell migration and proliferation in MG-63 cells. In addition, Adamopoulos et al Signal transduction in osteosarcoma 1301 stable downregulation of Polycystic Kidney Disease 1 gene in MG-63 cells enhances cell proliferation and affects proper cell differentiation, alterations mediated through impaired intracellular calcium-cAMP regulation, and activation of PKA.…”
Section: Mechanotransduction and Os Developmentmentioning
confidence: 99%
“…This is believed to play a major role in the invasion and metastasis of tumor cells[49,57]. Gargalionis et al[58] report that overexpression of the epithelial polycystins PC1 and PC2 in a human colon carcinoma cell line, HCT116, is able to induce EMT-related alteration in E-cadherin, N-cadherin, Snail and Twist (EMT trigger) mRNA expression. PC2 exogenous expression was also found to increase cell migration[58].…”
Section: Pathophysiology Of Colorectal Pcmentioning
confidence: 99%
“…A particularly unexpected finding was that the rate of non-kidney cancer was also lower in patients with ADPKD than in those without (adjusted IRR 0.83–0.84, P <0.0001). Similarly, a 2011 study suggested that a loss-of-function mutation in the ARPKD-associated gene PKHD1 (which encodes fibrocystin) provides protection against colorectal cancer [213], whereas a 2014 study indicated that overexpression of intact polycystin 1 or polycystin 2 promotes colorectal cancer aggressiveness [214]. …”
Section: Cancer In Adpkd; Cysts In Rccmentioning
confidence: 99%